2019
DOI: 10.1007/s12015-019-09922-2
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Directions of Stem Cell Therapy for Bladder Dysfunction

Abstract: Stem cells are capable of self-renewal and differentiation into a range of cell types and promote the release of chemokines and progenitor cells necessary for tissue regeneration. Mesenchymal stem cells are multipotent progenitor cells with enhanced proliferation and differentiation capabilities and less tumorigenicity than conventional adult stem cells; these cells are also easier to acquire. Bladder dysfunction is often chronic in nature with limited treatment modalities due to its undetermined pathophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 87 publications
(86 reference statements)
0
29
0
Order By: Relevance
“…The clinical efficacy and safety of intradetrusor injections of autologous muscle-derived cells for UAB were reported in a pilot study with humans [37]. Stem cells can restore the urethral sphincter function, and several clinical trials have shown the potential of stem cell therapy for managing SUI [38]. Although there is currently insufficient evidence, the application of stem cell therapy to both detrusor smooth muscle and urethral sphincter smooth muscle may be used to treat UAB patients with incontinence.…”
Section: Future Therapiesmentioning
confidence: 99%
“…The clinical efficacy and safety of intradetrusor injections of autologous muscle-derived cells for UAB were reported in a pilot study with humans [37]. Stem cells can restore the urethral sphincter function, and several clinical trials have shown the potential of stem cell therapy for managing SUI [38]. Although there is currently insufficient evidence, the application of stem cell therapy to both detrusor smooth muscle and urethral sphincter smooth muscle may be used to treat UAB patients with incontinence.…”
Section: Future Therapiesmentioning
confidence: 99%
“…It has been widely reported that stem cells can motivate the ECM reconstruction of the urethral sphincter to promote the recovery of urethral function in SUI [ 13 16 ]. Among the stem cells that have been studied, bone marrow mesenchymal stem cells (BMMSC) are the most widely used stem cells in tissue repair and regenerative medicine due to their universal source, self-renewal capacity in vitro, and low immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, our review discusses the possible approaches for applying stem cells (ASCs and PSCs) in bladder regeneration and IC/BPS therapy, which are summarized in Table 1. Many preclinical studies demonstrate biosafety and the potential of stem cells to treat bladder diseases [221]. As described above, the therapeutic potentials of ASCs and PSCs in bladder regeneration are attributed to their ability to differentiate into key bladder cells, such as urothelium and SMCs.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%